2013
DOI: 10.1097/bot.0b013e31828afde4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results and Costs of Muscle Flap Coverage With Ilizarov Bone Transport in Lower Limb Salvage

Abstract: The long-term results and costs of bone transport and flap coverage strongly support complex limb salvage in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 26 publications
1
52
0
2
Order By: Relevance
“…2,3,32,33 However, it remains indisputable that the main disadvantage of the Ilizarov technique is the tedious process with external fixation that may take months to perform. Intense pin-track pain appeared in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,32,33 However, it remains indisputable that the main disadvantage of the Ilizarov technique is the tedious process with external fixation that may take months to perform. Intense pin-track pain appeared in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lowenberg et al [15] reported a rate of 8.8% for docking-side nonunion even though they performed autogenous bone grafting at the docking side. Cierney and Zorn [16] recommended the use of an autogenous bone graft in cases of nonunion with more than 60 mm segmental bone loss defect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conversion to internal fixation must avoid any iatrogenic contamination and be strong enough to stabilize the immature bone (regenerate) [1,9,25,28,39,41]. The onerous patient experience with traditional Ilizarov reconstruction is a powerful way to completely restore nearnormal anatomy and restoration of function in a cost-effective manner [23]. Improvement in the patient's treatment experience, through minimizing external fixator-related complications, should result in better patient outcomes; however, this needs to be supported by comparative studies.…”
Section: Discussionmentioning
confidence: 99%